Network Analysis of Research Collaboration in Skills-Based Leadership: A Bibliometric Approach - Judijanto, Loso; Suryadi, Irwan; Tanjung, Rahman (Westscience Press, 2024)
Skills-based leadership has emerged as a critical area of study within the realm of organizational behavior and management theory. This paper employs a bibliometric approach to analyze the landscape of research collaboration in skills-based leadership. Utilizing network analysis techniques, the paper explores the patterns of collaboration among researchers, institutions, and countries, shedding light on the dynamics and evolution of this field. By synthesizing bibliometric data, this study aims to provide insights into the structure, trends, and key contributors in research on skills-based leadership, offering valuable implications for future research directions and practical applications.